THE CAUCASIAN DIMENSION OF THE EASTERN PARTNERSHIP IN 2009-2016 - P. A. Barakhvostov (MGIMO University Press, 2016)
The paper gives an in-depth analysis of the evolution of the EU policy towards the South Caucasus within the framework of the Eastern Partnership. It is amply demonstrated that in 2009-2016 the goal was a Europeanization as a creation of a favorable external environment for the European Union through a sweeping judiciary, economic and political transformation in the region carried out according to the European standards. Among the key objectives of the European Union policy is the maintenance of energy security by means of creating an alternative transport corridor for fossil fuels. The study underscores that the implementation of the Eastern Partnership in 2009-2013 revealed significant discrepancies in the speed and degree of Europeanization in the South Caucasus countries due to their socio-economic peculiarities. Such uneven transformation reflects the long-standing search for an optimum way of cooperation with the European Union. This complex multi-aspect and long-term process constitutes an integral part of the effort to grasp new national and regional identities made by post-Soviet states. The paper thoroughly analyses the distinctive features of the new EU foreign policy strategy characterized by a differentiated approach to each country. Instead of the former irreciprocal statement of prerequisites for cooperation, such an approach paves the way for meaningful bilateral dialogue between the partners and furthers integration just to the extent they are ready for. Yet, it is shown that this strategy preserved the faults of the former EU regional policy towards the post-Soviet space. They include inconsistency, vague objectives, and emphasis on the geopolitical confrontation with Russia. However, in order to promote the stable development of the region, the EU needs to rethink its foreign policy strategy and come up with a modernized framework of cooperation that would take into account the interests of all concerned parties, including the Russian Federation.